Pengaruh Pajak Hotel dan Pajak Restoran terhadap Pendapatan Asli Daerah: Studi Kasus di Provinsi Sumatera Barat - Dona, Elva (JURNAL PUNDI, 2025)
This study investigates the impact of hotel and restaurant taxes on locally generated revenue (Pendapatan Asli Daerah, PAD) in West Sumatra Province, Indonesia. As tourism and the service sector grow in the region, local governments increasingly rely on tax revenues from hospitality industries to fund public services and infrastructure. Using panel data from 19 districts and municipalities between 2016 and 2019, this study applies a fixed-effects regression model to analyze the influence of hotel and restaurant taxes on PAD. The findings reveal a statistically significant and positive relationship between these tax revenues and local government income, indicating their essential role in regional fiscal sustainability. Moreover, the study underscores the need for improved tax administration and strategic policy measures to enhance compliance and revenue performance. The results contribute to the broader discourse on subnational fiscal autonomy in emerging economies and offer